2022
DOI: 10.4274/jtgga.galenos.2022.2022-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B<sub>3</sub> (niacin), B<sub>6</sub>, C, and iron intake are associated with the free androgen index, especially in normoandrogenic polycystic ovary syndrome

Abstract: Objective: Nutritional intake is one of the most common environmental risk factors for polycystic ovary syndrome (PCOS) because it is associated with obesity and insulin resistance. The aim of this study was to determine the relationship between micronutrient intake and androgen levels associated with PCOS. Material and Methods: This cross-sectional study was performed in patients with PCOS divided into two groups, normoandrogenic (NA) and hyperandrogenic (HA), and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Either serum Ca showed positive correlation with serum Fe and Cu in group Y. The influence of Mg, Fe and Ca levels on pathology of PCOS remains unclear [32]. In many articles level of Mg and Fe was slightly higher or elevated in women with PCOS and Ca was reduced [30,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Either serum Ca showed positive correlation with serum Fe and Cu in group Y. The influence of Mg, Fe and Ca levels on pathology of PCOS remains unclear [32]. In many articles level of Mg and Fe was slightly higher or elevated in women with PCOS and Ca was reduced [30,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that vitamin C supplementation can have protective effects against PCOS-related ovarian pathophysiology, reduce oxidative stress markers, cytokines, and estrogen levels, and increase antioxidant and metabolic enzymes[70]. Combined intake of vitamin C with other nutrients like Vitamin B3 (niacin), B6, and iron has also been associated with improvements in the free androgen index in normoandrogenic PCOS[71]. Co-supplementation of vitamin C with Actaea racemosa (Black cohosh) plant extract has shown bene cial impacts on antioxidant status, hormonal pro le, lipid pro le,…”
mentioning
confidence: 99%